Women Artists and Artisans in Venice and the Veneto, 1400-1750: Uncovering the Female Presence - Cooper, Tracy (Visual and Material Culture, 1300-1700, 2024)
This book of essays highlights the lives, careers, and works of art of women artists and artisans in Venice and its territories from the fourteenth to the eighteenth centuries. The collection represents the first fruits of an ongoing research program launched by Save Venice, Inc., Women Artists of Venice, directed by Professor Tracy Cooper of Temple University, in conjunction with a conservation program, led by Melissa Conn, Director of Save Venice, Inc. Inspired by a growing body of research that has resurrected female artists and artisans in Florence and Bologna during the last decade, the Save Venice project seeks to recover the history of women artists and artisans born or active in the Venetian republic in the early modern period. Topics include their contemporary reception — or historical silence — and current scholarship positioning them as individuals and as an underrepresented category in the history of art and cultural heritage.